Phylogenetic Analysis of Antibiotic Resistance Genes and Virulence Genes of Klebsiella species in silico - Nahar, Nusrat; Rashid, Ridwan Bin (Dhaka University Journal of Pharmaceutical Sciences, 2017)
A total of twelve isolates were screened for virulence and antibiotic resistance genes associated with Klebsiella pneumoniae infections. Virulence and antibiotic resistance genes were detected by in silico PCR amplification. Iron uptake protein entB was detected in 66.67% (n=8) of the isolates while no isolate was found to harbour chelating agent irp2. Iron uptake system kfu, involved in purulent tissue infections and capsule formation, was identified in 25% (n=3) of the isolates. Regulator of mucoid phenotype A, rmpA was not found in any of the isolates. The wabG gene, responsible for urinary tract infections was found in seven K. pneumoniae strains. Five uge positive strains might play role in the pathogenicity of K. pneumoniae infections. About 83.33% of the isolates were positive for type 1 fimbriae fimH1 while no type 3 fimbriae mrkD gene was found. Complement reaction blocked by plasmid traT gene was not observed in Klebsiella species while eight isolates harboured outer membrane lipoprotein, ycfM which protects Klebsiella species from antibiotics. Antibiotic resistance genes blaTEM and blaSHV were detected in 33.33% (n=4) and 66.67% (n=8) of the isolates while 25% isolates carried both blaTEM and blaSHV genes. Genotype 1 carried fimH1 and ycfM genes while all the virulence genes studied were present in genotype 2 and 3. The blaSHV gene was detected in all the genotypes while blaTEM gene was found in only genotype 1 and 3. The findings of this study would be helpful to predict virulence gene associated with Klebsiella infections. This data also helps us to choose antibiotics for treating Klebsiella infections. By assessing the genotypic distribution of antibiotic resistance gene, correct antibiotic can be used to treat the infection. This could help reduce emergence of antibiotic resistance since it is known that incorrect choice of antibiotics contributes to antibiotic resistance. Dhaka Univ. J. Pharm. Sci. 16(1): 119-127, 2017 (June)